2019
DOI: 10.3390/f10121076
|View full text |Cite
|
Sign up to set email alerts
|

Biochar Is Comparable to Dicyandiamide in the Mitigation of Nitrous Oxide Emissions from Camellia oleifera Abel. Fields

Abstract: Research Highlights: Intensive nitrogen (N) application for agricultural purposes has substantially increased soil nitrous oxide (N2O) emissions. Agricultural soil has great potential in the reduction of N2O emissions, and applications of biochar and nitrification inhibitors may be useful for mitigating agricultural soil N2O emissions. Background and Objectives: Camellia oleifera Abel. is an important woody oil plant in China. However, intensive N input in C. oleifera silviculture has increased the risk of soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…In addition, nutrient management in forest ecosystems should consider the ecological effects of fertilization under the context of global climate change, considering the potential interactions among global change factors [93,94], nutrient input [95], and internal element cycling within forest ecosystems [96][97][98][99][100][101]. For example, in plantations experiencing intensive management, N input may induce more N leaching due to excessive application, especially in areas characterized by acid soils [101,102]. To prevent such N loss from soil to happen, soil amelioration should be employed to decrease N leaching via runoffs, trace gas emissions, or volatilization [102,103], increasing the fertilization efficiency of agricultural practice [101,102].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, nutrient management in forest ecosystems should consider the ecological effects of fertilization under the context of global climate change, considering the potential interactions among global change factors [93,94], nutrient input [95], and internal element cycling within forest ecosystems [96][97][98][99][100][101]. For example, in plantations experiencing intensive management, N input may induce more N leaching due to excessive application, especially in areas characterized by acid soils [101,102]. To prevent such N loss from soil to happen, soil amelioration should be employed to decrease N leaching via runoffs, trace gas emissions, or volatilization [102,103], increasing the fertilization efficiency of agricultural practice [101,102].…”
Section: Resultsmentioning
confidence: 99%
“…For example, in plantations experiencing intensive management, N input may induce more N leaching due to excessive application, especially in areas characterized by acid soils [101,102]. To prevent such N loss from soil to happen, soil amelioration should be employed to decrease N leaching via runoffs, trace gas emissions, or volatilization [102,103], increasing the fertilization efficiency of agricultural practice [101,102]. Presently, biochar has been widely used in soil amelioration or mitigation of soil trace gas (especially those containing N) [103,104].…”
Section: Resultsmentioning
confidence: 99%
“…The alteration in both C and N status by intensive management of C. oleifera plantation indicated potential impact on C and N content in underneath soils [22]. As an important non-timber woody oil plant, C. oleifera has been widely planted and intensively cultivated in subtropical China [12,13]. Intensive management practice in C. oleifera plantations generally including tillage, grass control, fertilization, thinning or removing other tree or grass species [14,15,22], converting C. oleifera plantations from mixed plantations to pure plantations.…”
Section: Changes In Soil C N and P As Affected By Plantation Typesmentioning
confidence: 99%
“…While most studies focused on forests producing timber or providing service [11], the intensive management of woody oil plant, Camellia oleifera, which could produce high-quality edible oil from its fruit has not been thoroughly studied [12][13][14]. The main distribution area of C. oleifera is red soil area in subtropical China, especially Jiangxi and Hunan province [12,14]. Plantations of C. oleifera could be managed in hilly areas with lower nutrients that are not suitable for development of agricultural farmland [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The study of Criscuoli et al in northern Italy showed that conifer woodchip-derived biochar application did not significantly influence the temperature sensitivity of soil CO 2 and N 2 O emissions, but significantly reduced the sensitivity of soil CH 4 uptake [25]. In the second biochar study included in this Special Issue, Deng et al conducted an in situ experiment to examine the effects of shell-derived biochar and dicyandiamide (DCD) on soil N 2 O emissions from a tea oil camellia (Camellia oleifera Abel) plantation with intensive N application in Jiangxi province, China [26]. The authors found that N application enhanced cumulative soil N 2 O emissions by 307%, adding biochar and DCD to the N-fertilized field reduced cumulative soil N 2 O emissions by 36 and 44%, respectively, suggesting that the mitigation potential of biochar on soil N 2 O emissions may reach that of DCD under the conditions studied [26].…”
mentioning
confidence: 99%